IMPLEMENTASI NILAI KEMANUSIAAN DALAM MENYIKAPI PELANGGARAN ETIKA DIGITAL SISWA KELAS X AKUNTANSI DAN KEUANGAN LEMBAGA DI SMKN 2 BOYOLANGU - Istanti, Yuli; Agustina Rahayu, Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of information and communication technology has brought serious challenges to the younger generation, particularly in terms of digital behavior. Violations of digital ethics such as cyberbullying, hate speech, and the spread of negative content are increasingly prevalent, requiring responses based on humanitarian values. This study aims to describe the implementation of humanitarian values in addressing violations of digital ethics and to identify the obstacles and efforts made by schools. This research employed a qualitative approach with a descriptive research design. The subjects of the study were students of class X Accounting and Institutional Finance, Civics Education teachers, homeroom teachers, and Guidance and Counseling teachers at SMKN 2 Boyolangu. Data were collected through observation, in-depth interviews, and documentation. The data analysis technique used an interactive analysis model, while data validity was tested through source and technique triangulation. The results showed that: (1) students had demonstrated several indicators of the implementation of humanitarian values, such as helping one another, showing tolerance among peers, and using relatively polite language. However, students’ active responses toward digital ethics violations, such as rejecting unethical behavior in digital spaces, were still not optimal. (2) The school had made reinforcement efforts through Civics Education learning and student character development. The main obstacles faced included the influence of the digital environment that is difficult to control outside school, the unstable emotional condition of adolescents, and the uneven implementation of humanitarian values. This study concludes that the implementation of humanitarian values in the context of digital ethics in vocational schools requires a consistent and collaborative approach between schools and families. Strengthening digital literacy combined with Pancasila-based character education is the key to shaping students’ civilized and dignified digital behavior.